The interior decoration of four special libraries a case study - Carlos, Azenith F. (1999)
A library is the meeting place of people who search for knowledge. A haven where one can customarily read, research, study, and relax. A common place that needs a good study of interior design is essential. Lighting, cooling, space allocation, furniture arrangements, and acoustics are factors that, if overlooked can bring about discomfort to your users' lives.